Krisis ekonomi menuju reformasi total - Sjahrir, 1945- (Jakarta : Yayasan Obor Indonesia [dan] Yayasan Padi dan Kapas, 1998)
The current economic crisis in Indonesia, policies for economic and political reform.
Includes index.
Keywords: Indonesia -- Economic conditions -- 1945-; Indonesia -- Economic policy; Indonesia -- Politics and government -- 1966-1998.